EASYCHATBOT (CIPEEX, 2022)
IN ORDER TO EMULATE A PSYCHOTHERAPIST WHO INTERACTED AND ASKED QUESTIONS, PROGRAMMING SCIENTIST AND MIT RESEARCHER JOSEPH WEIZENBAUM DEVELOPED THE FIRST CHATBOT TO SIMULATE HUMAN INTERACTION: THE ELIZA SOFTWARE. WITH THE DEVELOPMENT OF COMPANIES THAT CONTINUE TO RUN WITH THE COMPONENTS OF THE YEARS SIMULATING NOT JUST THE FIELD OF PSYCHOLOGY EVERY TIME WITH THE SAME INTENT EVERY TIME IN ALMOST EVERY APPLICATION - AND COMPONENTS OF TODAY.THIS WORK IS THE CREATION OF ITS OWN PROGRAM FOR CUSTOMIZING A CHATBOT, NOT WHICH THE CONTRACTOR WILL HAVE TO CARRY OUT ONLY THE PART OF CUSTOMIZING THE COMPONENTS. HAVING THE BOT DEVELOPMENT EASIER FOR EACH COMPANY, CONSIDERING THE CHATBOT DEVELOPMENT TIME AND A REDUCTION OF IT, SO THE COMPANY CAN USE THE APPLICATION SO THAT THE OBJECTIVE IS TO FOCUS ON OTHER AREAS OF ITS WEBSITE OR WEBSITE. FOR YOUR CHAT CREATION, THE C# LANGUAGE WILL BE USED TO FORMULATE THE RETURN THAT WILL RECEIVE ALL THE OFFERS GRANTED TO THE FRONT-END, THUS FORMULATING THE SCREEN OF EACH BOT CUSTOMIZED BY THE COMPANIES. ON THE CLIENT SIDE, JAVASCRIPT WILL BE USED AS PART OF THE HTML PROJECT, WHICH WILL BE USED AS THE FINAL PART AND THE CSS FOR THE FINAL CONSUMER. THE RESULTS WILL BE A CHANGE OF CHATBOT CUSTOMIZATION OF DYNAMIC TYPES, IN VIEW OF A CONSENSUS OF USE WITH A BACK-END FOCUSED ON RECEIVING THE USER'S CHOICES IN ORDER TO FORMULATE A PRODUCT THAT PLEASES THE MOST DIVERSE OF CONTRACTORS.